Anthropogenic Emissions from Combustion of Coal-Water Slurries Containing Petrochemicals Based on Coal and Oil Processing Wastes; Chemical and Petroleum Engineering; Vol. 54, iss. 1-2 - Kurgankina M. A. Margarita Aleksandrovna; Kosintsev A. G. Andrey Georgievich; Nyashina G. S. Galina Sergeevna; Lyrshchikov S. Yu. Sergey Yurievich (2018, 2018)
Title screen